Propozycja statystycznej metody zmiany poziomu wskaźników finansowych - Szpulak, Aleksandra (Proposal of The Financial Ratio Changes Statistical Analysis, 2008)
This article describes the way of doing the financial ratio analysis that might help to identify the reasons of existing changes in the financial ratio. This analysis can be used instead of or eventually additionally to tools traditionally used in financial ratios analysis. There is also a brief description of the financial ratios simulations, that is very useful for managers while directing the corporate finance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 537-547